O22.5 Providing Discrete and Reliable STD Testing in Alaska Via a Web-Based At-Home Service. (13th July 2013) - Simons, B; Jessen, C; Rea, L; Barnes, M; Barnes, P; Gaydos, C
Abstract : Background: Alaska has one of the highest rates of Chlamydia trachomatis (CT) and Neisseria gonorrhoeae (GC) in the United States. Alaska Native people, women and youth (ages 15–29) are disproportionately affected. Alaska Native health organisations have jurisdictions over large geographic areas, containing small isolated communities where a perceived lack of confidentiality and privacy is an identified barrier to accessing Sexually Transmitted Disease (STD) testing. The Alaska Native Tribal Health Consortium (ANTHC) has partnered with the " I Want the Kit " programme (IWTK) at Johns Hopkins University (JHU) to provide a discrete and reliable STD testing alternative. Methods: Alaska residents 14 years of age and older can request a no-cost STD testing kit online or by phone, which is mailed via U.S. Postal Service. After collection, the kit is returned in a prepaid envelope to JHU where it is tested for Chlamydia, gonorrhoea and Trichomonas . JHU reports all testing results to ANTHC, where a nurse notifies all participants of their results and refers positive cases for treatment. IWTK Alaska focuses its advertising efforts in rural Alaskan areas where the disease burden can be high and the barriers to accessing confidential healthcare are greatest. Results: In 2012, JHU received a total of 439 home testing kit requests from Alaska of which 161 (37%) were returned. Alaska Native and/or American Indian participants comprised 30% and Whites 53% of kits tested; other minority groups made up the remaining 17% of kits tested. The ages of individuals who returned kits ranged from 16 to 63 years, with a median age of 28 years. Among the 161 kits tested, 14 (8.6%) tested positive for Chlamydia, two of these also tested positive for gonorrhoea, and four kits were positive for Trichomonas. Conclusion: This web-based STD testing option increases access to STD testing by alleviating privacy and confidentiality concerns.